PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN KEPADA PELAKU TINDAK PIDANA PENGANIAYAAN - Monidar Buulolo (Jurnal Panah Hukum, 2025)
This research aims to determine the judge's considerations in handing down criminal decisions to perpetrators of criminal acts of abuse. The type of research used is normative legal research. One type of legal science known as normative law views the legal system as a system that uses and analyzes secondary data. Primary, secondary and tertiary data obtained from secondary legal texts are used in the data collection process. This research uses qualitative data analysis using descriptive methodology. Analyzing qualitative data involves examining well-gathered information without using numerical values. In this decision, it was determined that the defendant violated Article 351 paragraph (1) of the Criminal Code based on the findings of the investigation. Based on the evidence, post-mortem, witness statements, the defendant's statement, and the panel of judges' beliefs, the judge sentenced the defendant to five (five) months in prison. However, the results of the researcher's research show that the court was wrong in concluding that the defendant's actions should be considered serious maltreatment based on Article 351 paragraph (2) because the criteria for serious maltreatment had been met based on the chronology of the case.